Preparation method of aerogel material for thermal insulation oil pipe

Through the combination technology of silicon-aluminum composite gel and modified glass fiber felt, aerogel materials with excellent mechanical properties and low thermal conductivity were prepared, which solved the problem of insufficient application of existing aerogel thermal insulation materials in high temperature environments. , significantly improves the service life and thermal insulation performance of the thermal insulation pipe.

CN119080473BActive Publication Date: 2025-02-11SHANDONG MESHINE THERMAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411591958.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing aerogel thermal insulation materials are prone to deformity under high temperature environments and have a high thermal conductivity, which limits their application life and thermal insulation effect. Especially during long-term steam injection, the thermal insulation performance of thermal insulation oil pipes is rapidly reduced.

Method used

Using the combination technology of silicon-aluminum composite gel and modified glass fiber mat, aerogel materials with excellent mechanical properties and low thermal conductivity are prepared by preparing silicon-aluminum composite sol composite modified glass fiber mat.

Benefits of technology

It improves the service life and thermal insulation performance of the heat-insulating oil pipes, reduces thermal conductivity, and enhances the mechanical strength and high temperature stability of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of aerogel material preparation, and specifically relates to a method for preparing an aerogel material for an insulated oil pipe. The preparation method comprises the following steps: (1) preparing a first silica sol and a second silica sol; (2) preparing an alumina sol; (3) preparing a silica-alumina composite gel; (4) preparing a modified glass fiber felt; (5) preparing an aerogel material for an insulated oil pipe. The method for preparing an aerogel material for an insulated oil pipe of the present invention prepares an aerogel material by preparing a silica-alumina composite sol and compounding a modified glass fiber felt, so that the prepared aerogel material has the properties of high mechanical strength and low thermal conductivity, and can improve the service life of the insulated oil pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel material preparation, and specifically relates to a method for preparing an aerogel material for a heat-insulating oil pipe. Background Art

[0002] Insulated oil casing is an oil pipe with thermal insulation function used in steam injection to extract heavy oil. Insulated oil casing can reduce heat loss during crude oil lifting and ensure the efficiency of super heavy oil extraction. The existing insulating casing is divided into an inner tube and an outer tube. A layer of aerogel insulation layer will be filled between the inner and outer tubes. The aerogel insulation layer is used to insulate the heat of the injected steam and reduce heat loss.

[0003] At present, the insulated oil pipes used in multi-element thermal fluid huff and puff operations or steam huff and puff operations in offshore oil fields are mostly 4-1 / 2″ prestressed high vacuum insulated oil pipes. According to the industry standard of prestressed insulated oil pipes, the grade of the insulated oil pipes used is E grade, and the apparent thermal conductivity is between 0.002-0.006W / (m·℃). This type of insulated oil pipe has good thermal insulation performance in the early stage of use, but after a period of use, the vacuum degree of the insulation layer decreases due to hydrogen permeation and other reasons as the insulated oil pipe is used for a longer time, which will cause the apparent thermal conductivity of the insulated oil pipe to continue to increase. , the thermal insulation performance is greatly reduced. In addition, mechanical damage, severe corrosion, etc. may also directly lead to the performance failure of the insulated oil pipe. The continuous steam injection time of steam or multi-component thermal fluid throughput is short, and the high vacuum insulated oil pipe can meet the steam injection requirements. Aerogel is a lightweight porous material composed of nano-scale particles and air as the dispersion medium. It has unique optical, thermal and electrical properties. It is currently the best thermal insulation performance and the lightest solid material. Placing the aerogel insulation material in the annular cavity between the inner casing and the outer casing of the insulated oil pipe can improve the thermal insulation performance of the oil pipe.

[0004] However, the existing aerogel insulation materials have relatively high thermal conductivity and are easily deformed after being heated, which limits their application in high temperature environments. Moreover, as the steam injection cycle and injection time increase, the insulation effect of the insulated oil pipe decreases rapidly, causing the insulated oil pipe to be scrapped and the heavy oil thermal recovery efficiency to decrease. Therefore, it is necessary to explore a new type of aerogel material to improve the insulation life of the insulated oil pipe. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an aerogel material for insulating oil pipes. The aerogel material prepared by the method has excellent mechanical properties and thermal insulation properties.

[0006] The method for preparing the aerogel material for insulating oil pipe of the present invention comprises the following steps:

[0007] (1) mixing a silicon source precursor, deionized water and isopropanol uniformly, adding hydrochloric acid to adjust the pH value of the system to 3.0-3.5, stirring at room temperature for 20-21 hours to obtain a silica sol, wherein the silica sol is composed of a first silica sol and a second silica sol, and the silicon source precursor is a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane;

[0008] (2) adding aluminum isopropoxide to deionized water and reacting it at 81-83°C with magnetic stirring for 2.5-2.8 hours, adding anhydrous ethanol as a dispersant, and then adding nitric acid and F127 solution to dissolve and disperse the sol, removing anhydrous ethanol for 20-25 minutes after the sol is clarified, and then refluxing it at 90-93°C with magnetic stirring for 4 hours to prepare an alumina sol;

[0009] (3) dissolving the first silica sol in the alumina sol and stirring the mixture for 12-13 hours, then adding epichlorohydrin and continuing to stir for 12-15 minutes to prepare a silica-alumina composite gel;

[0010] (4) dissolving polyvinylidene fluoride fiber, polyarylate fiber, zirconium oxide whisker and the second silica sol prepared in step (1) in deionized water and stirring evenly to prepare a mixed solution, placing a glass fiber mat in a mold, and then pouring the prepared mixed solution into the mold for vacuum impregnation, freezing treatment, and vacuum drying to prepare a modified glass fiber mat;

[0011] (5) The prepared silica-alumina composite gel is poured into a mold containing modified glass fiber felt, and the silica-alumina composite gel covers the modified glass fiber felt for impregnation, and then the gel is allowed to stand. Finally, ethanol aging liquid is added to the mold for aging and drying, thereby preparing an aerogel material for insulating oil pipes.

[0012] in:

[0013] In step (1), the molar ratio of the silicon source precursor, deionized water and isopropanol is 1:4:4, and the mass ratio of vinylmethyldimethoxysilane to bis(methyldimethoxysilyl)methane in the silicon source precursor is 4:1.

[0014] In step (1), the mass ratio of the first silica sol to the second silica sol is 5:1.

[0015] In step (2), the molar ratio of aluminum isopropoxide to deionized water is 1:48.

[0016] The molar ratio of anhydrous ethanol to deionized water in step (2) is 1:85.

[0017] The concentration of nitric acid in step (2) is 1.5 mol / L, and the volume ratio of nitric acid to deionized water is 1:5.0.

[0018] The concentration of the F127 solution in step (2) is 20 g / L, the volume ratio of the F127 solution to deionized water is 1:5.8, F127 is a PEO-PPO-PEO triblock copolymer, and the manufacturer is Shanghai Huzhen Industrial Co., Ltd.

[0019] In step (3), the molar ratio of silicon to aluminum when the first silica sol and the alumina sol are stirred and mixed is 7-8:1.

[0020] In step (3), the molar ratio of the first silica sol to epichlorohydrin is 1:4.5-5.

[0021] In step (4), the mass ratio of polyvinylidene fluoride fiber, polyarylate fiber and zirconium oxide whisker is 1:0.3-0.5:0.05-0.07.

[0022] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, and the zirconium oxide whisker to the mass ratio of the second silica sol is 1:10-11.

[0023] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, the zirconium oxide whisker to the second silica sol and to the deionized water is 1:8-9.

[0024] The vacuum impregnation time in step (4) is 3-4 hours.

[0025] In step (4), the freezing treatment temperature is -10°C and the freezing treatment time is 44h.

[0026] In step (4), the vacuum drying temperature is -30°C and the vacuum drying time is 50h.

[0027] The gel time in step (5) is 22-23 hours, and the gel temperature is room temperature.

[0028] In step (5), the aging solution is first replaced every 8 hours for a total of 3 times, and then the aging solution is replaced every 12 hours for a total of 2 times.

[0029] In step (5), the aged wet gel is placed in an ethanol supercritical drying kettle for drying. The ethanol supercritical drying temperature is 268° C., the drying pressure is 9.5 MPa, and the drying time is 2 h.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The method for preparing aerogel material for insulating oil pipes described in the present invention prepares aerogel material by preparing a silicon-aluminum composite sol and compounding modified glass fiber felt, so that the prepared aerogel material has the properties of high mechanical strength and low thermal conductivity, which can increase the service life of the insulating oil pipe.

[0032] (2) In the preparation method of the aerogel material for insulating oil pipes described in the present invention, a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane is selected as a silicon source precursor when preparing silica sol. Vinylmethyldimethoxysilane has a bendable hydrocarbon chain in its molecular structure, which can ensure the compressive strength of the prepared silica gel skeleton. The addition of bis(methyldimethoxysilyl)methane can ensure the flexibility of the prepared silica gel; the combination of the two can intrinsically enhance the skeleton strength of the prepared silica sol.

[0033] (3) The method for preparing aerogel materials for insulating oil pipes described in the present invention is to compound silica sol and alumina sol to prepare silica-alumina composite sol and then use it as a skeleton to prepare aerogel materials because if silica sol is used alone, the network skeleton of the prepared silica aerogel is very thin at high temperature and is easily broken under the action of external force, causing the pore structure to be destroyed. Therefore, the composite alumina sol improves the high-temperature thermal insulation performance of the prepared aerosol, so that the finally prepared aerogel material has excellent mechanical properties and thermal insulation properties. In the preparation process of silica-alumina composite gel, epichlorohydrin is used to control its gelation process to be relatively mild, and it can ensure that the porosity and elasticity of the gel are not reduced.

[0034] (4) The method for preparing an aerogel material for insulating oil pipes described in the present invention comprises the following steps: the polyvinylidene fluoride fibers, polyarylate fibers and zirconium oxide whiskers are uniformly distributed in the pores of the glass fiber felt by vacuum impregnation in step (4); and the sol is then vacuum impregnated into the glass fiber felt containing the polyvinylidene fluoride fibers, polyarylate fibers and zirconium oxide whiskers after freezing treatment and vacuum drying to prepare a modified glass fiber felt, wherein the addition of the polyvinylidene fluoride fibers has hydrogen barrier properties, the polyarylate fibers can further reduce the thermal conductivity of the prepared aerogel material, and the zirconium oxide whiskers improve the mechanical properties of the prepared aerogel without increasing its thermal conductivity. DETAILED DESCRIPTION

[0035] The present invention is further described below with reference to the embodiments.

[0036] Example 1

[0037] The method for preparing the aerogel material for the heat-insulating oil pipe described in Example 1 comprises the following steps:

[0038] (1) mixing a silicon source precursor, deionized water and isopropanol uniformly, adding hydrochloric acid to adjust the pH value of the system to 3.3, and stirring at room temperature for 20.5 hours to obtain a silica sol, wherein the silica sol consists of a first silica sol and a second silica sol, and the silicon source precursor is a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane;

[0039] (2) Aluminum isopropoxide was added to deionized water and reacted at 82°C with magnetic stirring for 2.6 hours, anhydrous ethanol was added as a dispersant, and then nitric acid and F127 solution were added to dissolve and disperse the sol. After the sol was clarified, the anhydrous ethanol was removed for 23 minutes, and then the sol was refluxed at 91°C with magnetic stirring for 4 hours to prepare an alumina sol;

[0040] (3) dissolving the first silica sol in the alumina sol and stirring the mixture for 12.5 hours, then adding epichlorohydrin and continuing to stir for 13 minutes to prepare a silica-alumina composite gel;

[0041] (4) dissolving polyvinylidene fluoride fiber, polyarylate fiber, zirconium oxide whisker and the second silica sol prepared in step (1) in deionized water and stirring evenly to prepare a mixed solution, placing a glass fiber mat in a mold, and then pouring the prepared mixed solution into the mold for vacuum impregnation, freezing treatment, and vacuum drying to prepare a modified glass fiber mat;

[0042] (5) The prepared silica-alumina composite gel is poured into a mold containing modified glass fiber felt, and the silica-alumina composite gel covers the modified glass fiber felt for impregnation, and then the gel is allowed to stand. Finally, ethanol aging liquid is added to the mold for aging and drying, thereby preparing an aerogel material for insulating oil pipes.

[0043] in:

[0044] In step (1), the molar ratio of the silicon source precursor, deionized water and isopropanol is 1:4:4, and the mass ratio of vinylmethyldimethoxysilane to bis(methyldimethoxysilyl)methane in the silicon source precursor is 4:1.

[0045] In step (1), the mass ratio of the first silica sol to the second silica sol is 5:1.

[0046] In step (2), the molar ratio of aluminum isopropoxide to deionized water is 1:48.

[0047] The molar ratio of anhydrous ethanol to deionized water in step (2) is 1:85.

[0048] The concentration of nitric acid in step (2) is 1.5 mol / L, and the volume ratio of nitric acid to deionized water is 1:5.0.

[0049] The concentration of the F127 solution in step (2) is 20 g / L, the volume ratio of the F127 solution to deionized water is 1:5.8, F127 is a PEO-PPO-PEO triblock copolymer, and the manufacturer is Shanghai Huzhen Industrial Co., Ltd.

[0050] In step (3), the molar ratio of silicon to aluminum when the first silica sol and the alumina sol are stirred and mixed is 7.5:1.

[0051] In step (3), the molar ratio of the first silica sol to epichlorohydrin is 1:4.7.

[0052] In step (4), the mass ratio of polyvinylidene fluoride fiber, polyarylate fiber and zirconium oxide whisker is 1:0.4:0.06.

[0053] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, and the zirconium oxide whisker to the mass ratio of the second silica sol is 1:10.5.

[0054] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, the zirconium oxide whisker to the second silica sol and to the deionized water is 1:8.5.

[0055] The vacuum impregnation time in step (4) is 3.5 h.

[0056] In step (4), the freezing treatment temperature is -10°C and the freezing treatment time is 44h.

[0057] In step (4), the vacuum drying temperature is -30°C and the vacuum drying time is 50h.

[0058] The gel time in step (5) is 22.5 h and the gel temperature is room temperature.

[0059] In step (5), the aging solution is first replaced every 8 hours for a total of 3 times, and then the aging solution is replaced every 12 hours for a total of 2 times.

[0060] In step (5), the aged wet gel is placed in an ethanol supercritical drying kettle for drying. The ethanol supercritical drying temperature is 268° C., the drying pressure is 9.5 MPa, and the drying time is 2 h.

[0061] According to tests, the thermal conductivity of the aerogel material prepared in Example 1 is 0.0195 W / (m·K) and the compressive strength is 3.5 MPa.

[0062] Example 2

[0063] The method for preparing the aerogel material for the heat-insulating oil pipe described in Example 2 comprises the following steps:

[0064] (1) mixing a silicon source precursor, deionized water and isopropanol uniformly, adding hydrochloric acid to adjust the pH value of the system to 3.0, and stirring at room temperature for 20 hours to obtain a silica sol, wherein the silica sol consists of a first silica sol and a second silica sol, and the silicon source precursor is a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane;

[0065] (2) Aluminum isopropoxide was added to deionized water and reacted at 81°C with magnetic stirring for 2.8 hours, anhydrous ethanol was added as a dispersant, and then nitric acid and F127 solution were added to dissolve and disperse the sol. After the sol was clarified, the anhydrous ethanol was removed for 20 minutes, and then the sol was refluxed at 90°C with magnetic stirring for 4 hours to prepare an alumina sol;

[0066] (3) dissolving the first silica sol in the alumina sol and stirring the mixture for 12 hours, then adding epichlorohydrin and continuing to stir the mixture for 12 minutes to prepare a silica-alumina composite gel;

[0067] (4) dissolving polyvinylidene fluoride fiber, polyarylate fiber, zirconium oxide whisker and the second silica sol prepared in step (1) in deionized water and stirring evenly to prepare a mixed solution, placing a glass fiber mat in a mold, and then pouring the prepared mixed solution into the mold for vacuum impregnation, freezing treatment, and vacuum drying to prepare a modified glass fiber mat;

[0068] (5) The prepared silica-alumina composite gel is poured into a mold containing modified glass fiber felt, and the silica-alumina composite gel covers the modified glass fiber felt for impregnation, and then the gel is allowed to stand. Finally, ethanol aging liquid is added to the mold for aging and drying, thereby preparing an aerogel material for insulating oil pipes.

[0069] in:

[0070] In step (1), the molar ratio of the silicon source precursor, deionized water and isopropanol is 1:4:4, and the mass ratio of vinylmethyldimethoxysilane to bis(methyldimethoxysilyl)methane in the silicon source precursor is 4:1.

[0071] In step (1), the mass ratio of the first silica sol to the second silica sol is 5:1.

[0072] In step (2), the molar ratio of aluminum isopropoxide to deionized water is 1:48.

[0073] The molar ratio of anhydrous ethanol to deionized water in step (2) is 1:85.

[0074] The concentration of nitric acid in step (2) is 1.5 mol / L, and the volume ratio of nitric acid to deionized water is 1:5.0.

[0075] The concentration of the F127 solution in step (2) is 20 g / L, the volume ratio of the F127 solution to deionized water is 1:5.8, F127 is a PEO-PPO-PEO triblock copolymer, and the manufacturer is Shanghai Huzhen Industrial Co., Ltd.

[0076] In step (3), the molar ratio of silicon to aluminum when the first silica sol and the alumina sol are stirred and mixed is 7:1.

[0077] In step (3), the molar ratio of the first silica sol to epichlorohydrin is 1:4.5.

[0078] In step (4), the mass ratio of polyvinylidene fluoride fiber, polyarylate fiber and zirconium oxide whisker is 1:0.3:0.05.

[0079] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, and the zirconium oxide whisker to the mass ratio of the second silica sol is 1:10.

[0080] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, the zirconium oxide whisker to the second silica sol and to the deionized water is 1:8.

[0081] The vacuum impregnation time in step (4) is 3 hours.

[0082] In step (4), the freezing treatment temperature is -10°C and the freezing treatment time is 44h.

[0083] In step (4), the vacuum drying temperature is -30°C and the vacuum drying time is 50h.

[0084] In step (5), the gel time is 22 h and the gel temperature is room temperature.

[0085] In step (5), the aging solution is first replaced every 8 hours for a total of 3 times, and then the aging solution is replaced every 12 hours for a total of 2 times.

[0086] In step (5), the aged wet gel is placed in an ethanol supercritical drying kettle for drying. The ethanol supercritical drying temperature is 268° C., the drying pressure is 9.5 MPa, and the drying time is 2 h.

[0087] According to tests, the thermal conductivity of the aerogel material prepared in Example 2 is 0.0197 W / (m·K) and the compressive strength is 3.2 MPa.

[0088] Example 3

[0089] The method for preparing the aerogel material for the heat-insulating oil pipe described in Example 3 comprises the following steps:

[0090] (1) mixing a silicon source precursor, deionized water and isopropanol uniformly, adding hydrochloric acid to adjust the pH value of the system to 3.5, and stirring at room temperature for 21 hours to obtain a silica sol, wherein the silica sol consists of a first silica sol and a second silica sol, and the silicon source precursor is a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane;

[0091] (2) Aluminum isopropoxide was added to deionized water and reacted at 83°C with magnetic stirring for 2.5 hours, anhydrous ethanol was added as a dispersant, and then nitric acid and F127 solution were added to dissolve and disperse the sol. After the sol was clarified, the anhydrous ethanol was removed for 25 minutes, and then the sol was refluxed at 93°C with magnetic stirring for 4 hours to prepare an alumina sol;

[0092] (3) dissolving the first silica sol in the alumina sol and stirring the mixture for 13 hours, then adding epichlorohydrin and continuing to stir the mixture for 15 minutes to prepare a silica-alumina composite gel;

[0093] (4) dissolving polyvinylidene fluoride fiber, polyarylate fiber, zirconium oxide whisker and the second silica sol prepared in step (1) in deionized water and stirring evenly to prepare a mixed solution, placing a glass fiber mat in a mold, and then pouring the prepared mixed solution into the mold for vacuum impregnation, freezing treatment, and vacuum drying to prepare a modified glass fiber mat;

[0094] (5) The prepared silica-alumina composite gel is poured into a mold containing modified glass fiber felt, and the silica-alumina composite gel covers the modified glass fiber felt for impregnation, and then the gel is allowed to stand. Finally, ethanol aging liquid is added to the mold for aging and drying, thereby preparing an aerogel material for insulating oil pipes.

[0095] in:

[0096] In step (1), the molar ratio of the silicon source precursor, deionized water and isopropanol is 1:4:4, and the mass ratio of vinylmethyldimethoxysilane to bis(methyldimethoxysilyl)methane in the silicon source precursor is 4:1.

[0097] In step (1), the mass ratio of the first silica sol to the second silica sol is 5:1.

[0098] In step (2), the molar ratio of aluminum isopropoxide to deionized water is 1:48.

[0099] The molar ratio of anhydrous ethanol to deionized water in step (2) is 1:85.

[0100] The concentration of nitric acid in step (2) is 1.5 mol / L, and the volume ratio of nitric acid to deionized water is 1:5.0.

[0101] The concentration of the F127 solution in step (2) is 20 g / L, the volume ratio of the F127 solution to deionized water is 1:5.8, F127 is a PEO-PPO-PEO triblock copolymer, and the manufacturer is Shanghai Huzhen Industrial Co., Ltd.

[0102] In step (3), the molar ratio of silicon to aluminum when the first silica sol and the alumina sol are stirred and mixed is 8:1.

[0103] In step (3), the molar ratio of the first silica sol to epichlorohydrin is 1:5.

[0104] In step (4), the mass ratio of polyvinylidene fluoride fiber, polyarylate fiber and zirconium oxide whisker is 1:0.5:0.07.

[0105] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, and the zirconium oxide whisker to the mass ratio of the second silica sol is 1:11.

[0106] In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, the zirconium oxide whisker to the second silica sol and to the deionized water is 1:9.

[0107] The vacuum impregnation time in step (4) is 4 hours.

[0108] In step (4), the freezing treatment temperature is -10°C and the freezing treatment time is 44h.

[0109] In step (4), the vacuum drying temperature is -30°C and the vacuum drying time is 50h.

[0110] In step (5), the gel time is 23 h and the gel temperature is room temperature.

[0111] In step (5), the aging solution is first replaced every 8 hours for a total of 3 times, and then the aging solution is replaced every 12 hours for a total of 2 times.

[0112] In step (5), the aged wet gel is placed in an ethanol supercritical drying kettle for drying. The ethanol supercritical drying temperature is 268° C., the drying pressure is 9.5 MPa, and the drying time is 2 h.

[0113] After testing, the thermal conductivity of the aerogel material prepared in Example 3 is 0.0200 W / (m·K) and the compressive strength is 3.4 MPa.

[0114] Comparative Example 1

[0115] The preparation method of the aerogel material for insulating oil pipe described in this comparative example 1 consists of the following steps:

[0116] (1) The silicon source precursor, deionized water and isopropanol were mixed evenly, hydrochloric acid was added to adjust the pH value of the system to 3.3, and the reaction was stirred at room temperature for 20.5 hours to obtain silica sol. The silicon source precursor was a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane;

[0117] (2) Aluminum isopropoxide was added to deionized water and reacted at 82°C with magnetic stirring for 2.6 hours, anhydrous ethanol was added as a dispersant, and then nitric acid and F127 solution were added to dissolve and disperse the sol. After the sol was clarified, the anhydrous ethanol was removed for 23 minutes, and then the sol was refluxed at 91°C with magnetic stirring for 4 hours to prepare an alumina sol;

[0118] (3) Dissolving silica sol in alumina sol and stirring for 12.5 hours, then adding epichlorohydrin and continuing to stir for 13 minutes to prepare a silica-alumina composite gel;

[0119] (4) The prepared silica-alumina composite gel is poured into a mold containing glass fiber felt, and the silica-alumina composite gel covers the glass fiber felt for immersion, and then the gel is allowed to stand. Finally, ethanol aging liquid is added to the mold for aging and drying, thereby preparing an aerogel material for insulating oil pipes.

[0120] in:

[0121] In step (1), the molar ratio of the silicon source precursor, deionized water and isopropanol is 1:4:4, and the mass ratio of vinylmethyldimethoxysilane to bis(methyldimethoxysilyl)methane in the silicon source precursor is 4:1.

[0122] In step (2), the molar ratio of aluminum isopropoxide to deionized water is 1:48.

[0123] The molar ratio of anhydrous ethanol to deionized water in step (2) is 1:85.

[0124] The concentration of nitric acid in step (2) is 1.5 mol / L, and the volume ratio of nitric acid to deionized water is 1:5.0.

[0125] The concentration of the F127 solution in step (2) is 20 g / L, the volume ratio of the F127 solution to deionized water is 1:5.8, F127 is a PEO-PPO-PEO triblock copolymer, and the manufacturer is Shanghai Huzhen Industrial Co., Ltd.

[0126] In step (3), the molar ratio of silica to aluminum when the silica sol and the alumina sol are stirred and mixed is 7.5:1.

[0127] In step (3), the molar ratio of silica sol to epichlorohydrin is 1:4.7.

[0128] The gel time in step (4) is 22.5 h and the gel temperature is room temperature.

[0129] In step (4), the aging solution is first replaced every 8 hours for a total of 3 times, and then the aging solution is replaced every 12 hours for a total of 2 times.

[0130] In step (4), the aged wet gel is placed in an ethanol supercritical drying kettle for drying. The ethanol supercritical drying temperature is 268° C., the drying pressure is 9.5 MPa, and the drying time is 2 h.

[0131] According to tests, the thermal conductivity of the aerogel material prepared in Comparative Example 1 is 0.0314 W / (m·K) and the compressive strength is 2.5 MPa.

Claims

1. A method for preparing an aerogel material for insulating oil pipe, characterized in that: It consists of the following steps: (1) mixing a silicon source precursor, deionized water and isopropanol uniformly, adding hydrochloric acid to adjust the pH value of the system to 3.0-3.5, stirring at room temperature for 20-21 hours to obtain a silica sol, wherein the silica sol is composed of a first silica sol and a second silica sol, and the silicon source precursor is a mixture of vinylmethyldimethoxysilane and bis(methyldimethoxysilyl)methane; (2) adding aluminum isopropoxide to deionized water and reacting it at 81-83°C with magnetic stirring for 2.5-2.8 hours, adding anhydrous ethanol as a dispersant, and then adding nitric acid and F127 solution to dissolve and disperse the sol, removing anhydrous ethanol for 20-25 minutes after the sol is clarified, and then refluxing it at 90-93°C with magnetic stirring for 4 hours to prepare an alumina sol; (3) dissolving the first silica sol in the alumina sol and stirring the mixture for 12-13 hours, then adding epichlorohydrin and continuing to stir for 12-15 minutes to prepare a silica-alumina composite gel; (4) dissolving polyvinylidene fluoride fiber, polyarylate fiber, zirconium oxide whisker and the second silica sol prepared in step (1) in deionized water and stirring evenly to prepare a mixed solution, placing a glass fiber mat in a mold, and then pouring the prepared mixed solution into the mold for vacuum impregnation, freezing treatment, and vacuum drying to prepare a modified glass fiber mat; (5) pouring the prepared silicon-aluminum composite gel into a mold containing modified glass fiber felt, and making the silicon-aluminum composite gel cover the modified glass fiber felt for gel dipping, and then letting the gel stand, and finally adding ethanol aging liquid to the mold for aging and drying, to prepare an aerogel material for heat-insulating oil pipes; in: In step (1), the molar ratio of the silicon source precursor, deionized water and isopropanol is 1:4:4, and the mass ratio of vinylmethyldimethoxysilane to bis(methyldimethoxysilyl)methane in the silicon source precursor is 4:1; In step (1), the mass ratio of the first silica sol to the second silica sol is 5:1; In step (3), the molar ratio of silicon to aluminum when the first silica sol and the alumina sol are stirred and mixed is 7-8:1; In step (3), the molar ratio of the first silica sol to epichlorohydrin is 1:4.5-5.

2. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: In step (2), the molar ratio of aluminum isopropoxide to deionized water is 1:48; In step (2), the molar ratio of anhydrous ethanol to deionized water is 1:85; In step (2), the concentration of nitric acid is 1.5 mol / L, and the volume ratio of nitric acid to deionized water is 1:5.0; The concentration of the F127 solution in step (2) is 20 g / L, the volume ratio of the F127 solution to deionized water is 1:5.8, and F127 is a PEO-PPO-PEO triblock copolymer.

3. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: In step (4), the mass ratio of polyvinylidene fluoride fiber, polyarylate fiber and zirconium oxide whisker is 1:0.3-0.5:0.05-0.

07.

4. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, and the zirconium oxide whisker to the mass ratio of the second silica sol is 1:10-11.

5. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: In step (4), the mass ratio of the polyvinylidene fluoride fiber, the polyarylate fiber, the zirconium oxide whisker to the second silica sol and to the deionized water is 1:8-9.

6. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: The vacuum impregnation time in step (4) is 3-4 hours; In step (4), the freezing treatment temperature is -10°C and the freezing treatment time is 44h; In step (4), the vacuum drying temperature is -30°C and the vacuum drying time is 50h.

7. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: In step (5), the gel time is 22-23 hours and the gel temperature is room temperature; In step (5), the aging solution is first replaced every 8 hours for a total of 3 times, and then the aging solution is replaced every 12 hours for a total of 2 times.

8. The method for preparing aerogel material for heat-insulating oil pipe according to claim 1, characterized in that: In step (5), the aged wet gel is placed in an ethanol supercritical drying kettle for drying. The ethanol supercritical drying temperature is 268° C., the drying pressure is 9.5 MPa, and the drying time is 2 h.

Citation Information

Patent Citations

  • Silicon carbide fiber composite aerogel felt as well as preparation method and application thereof

    CN118324487A

  • Fibre-reinforced aerogel composites from mixed silica and rubber SOLS and a method to produce the rubber-silica aerogel composites

    WO2022259044A1